Terror Medicine as Part of the Medical School Curriculum - Cole, Leonard A.; Wagner, Katherine; Scott, Sandra; Connell, Nancy D.; Cooper, Arthur; Kennedy, Cheryl Ann; Natal, Brenda; Lamba, Sangeeta (Frontiers in Public Health, 2014)
Terror medicine, a field related to emergency and disaster medicine, focuses on medical issues ranging from preparedness to psychological manifestations specifically associated with terrorist attacks. Calls to teach aspects of the subject in American medical schools surged after the 2001 jetliner and anthrax attacks. Although the threat of terrorism persists, terror medicine is still addressed erratically if at all in most medical schools. This paper suggests a template for incorporating the subject throughout a 4-year medical curriculum. The instructional framework culminates in a short course for fourth year students, such as one recently introduced at Rutgers New Jersey Medical School, Newark, NJ. The proposed 4-year Rutgers curriculum serves as a model that could assist other medical schools contemplating the inclusion of terror medicine in pre-clerkship and clerkship training.